2012
DOI: 10.1094/mpmi-07-12-0179-r
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of Arabidopsis Inoculated with Alternaria brassicicola Reveals That Ascorbate Reduces Disease Severity

Abstract: The interaction between the pathogenic ascomycete Alternaria brassicicola and Arabidopsis was investigated by metabolite profiling. The effect of A. brassicicola challenge on metabolite levels was substantial, with nearly 50% of detected compounds undergoing significant changes. Mutations blocking ethylene, jasmonic acid, or ethylene signaling had little effect on metabolite levels. The effects of altering levels of some metabolites were tested by exogenous application during A. brassicicola inoculation. Gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 62 publications
3
52
0
1
Order By: Relevance
“…For A. brassicicola growth assays, at least 15 leaf discs from five to six plants were pooled per biological sample. Disease severity, a proxy of fungal growth, was determined as previously described (Tsuda et al, 2009;Botanga et al, 2012). For PME assays, at least four leaf discs from one plant were combined for each biological sample.…”
Section: Pathogen Strains Growth Conditions and Pathogen Growth Assaysmentioning
confidence: 99%
“…For A. brassicicola growth assays, at least 15 leaf discs from five to six plants were pooled per biological sample. Disease severity, a proxy of fungal growth, was determined as previously described (Tsuda et al, 2009;Botanga et al, 2012). For PME assays, at least four leaf discs from one plant were combined for each biological sample.…”
Section: Pathogen Strains Growth Conditions and Pathogen Growth Assaysmentioning
confidence: 99%
“…They observed both an increase and decrease in select organic acids and lipids, and an overall increase in potato alkaloids. An Arabidopsis-Alternaria brassicicola interaction study used non-targeted GC-MS and described 128 and 249 molecular features that varied after 9 and 24 h of infection including several sugars, organic acids, and amino acids (Botanga et al, 2012). …”
Section: Example Studies That Utilize Ms-metabolomics Workflows In Plmentioning
confidence: 99%
“…Total acorbic acid content in vtc1 clone is about 40% compared to wild type. Earlier work revealed that vtc1 mutant has increased resistance against Pseudomonas syringae or Peronospora parasitica [30] but more sensitive to Alternaria brassicicola [15].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Regulation of substrate pools such as glutathione or ascorbic acid is the key element of cell protection [11], and the capacity of the biochemical path sustaining the oxido-reductive potential of cells has crucial importance in elimination of harmful free radicals [12] and confers in resistance to pathogens [13,14]. The high level of ascorbic acid reduces the disease severity [15], while the deficiency increases the sensitivity to environmental stress factors [12]. Glutathione S-transferases play an important role in adaptation of various organisms to adverse factors [16][17][18], and in detoxification of electrophilic compounds either exogenic or of natural origin [19,20].…”
Section: Introductionmentioning
confidence: 99%